Gender differences in activity-limiting pain trajectories over a 17-year period in the Mexican Health and Aging Study. Issue 2 (7th April 2021) - Milani, Sadaf Arefi; Howrey, Bret; Rodriguez, Martin A.; Samper-Ternent, Rafael; Wong, Rebeca
Abstract : Supplemental Digital Content is Available in the Text. Older Mexicans had 2 trajectories of activity-limiting pain (low-stable and moderate-increasing) over 17 years. Compared with men, women were more likely to have moderate-increasing pain. Abstract: Pain increases with age, disproportionately affects women, and is a major contributor to decreased quality of life. Because pain is dynamic, trajectories are important to consider. Few studies have examined longitudinal trajectories of pain, by gender, in Mexico. We used data from 5 waves (over 2001–2018) of the Mexican Health and Aging Study, a nationally representative sample of Mexicans aged 50 years and older. Pain was categorized as self-reported frequent pain that makes it difficult to do usual activities. Latent class mixture models were used to create pain trajectories (n = 9824). The sample was majority female (56.15%), with a mean age of 61.72 years. We identified 2 pain trajectories: low-stable (81.88%) and moderate-increasing (18.12%). Women had 1.75 times the odds of being in the moderate-increasing group compared with men (95% confidence interval= 1.41, 2.17). In addition, having zero years of education was associated with higher odds of being in the moderate-increasing group, compared with having any years of education. Fair/poor self-rated health, obesity, arthritis, elevated depressive symptoms, and falls were positively associated with pain for both trajectory groups. Being married was positively associated with pain in the low-stable group. Insurance status was negatively associated with pain in the low-stable group, but positively associated with pain in the moderate-increasing group. We identified 2 trajectories of activity-limiting pain, among older Mexican adults (50+) over 17 years of follow-up. Understanding gender differences in pain trajectories in later life and the factors associated with trajectory development is crucial to improve quality of life, especially in vulnerable populations.